2022
DOI: 10.3390/ani12131695
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Digesta- and Mucosa-Associated Jejunal Microbiota of Hu Sheep to Pelleted and Non-Pelleted High-Grain Diets

Abstract: In the present study, we utilized 16S rRNA sequencing to uncover the impacts of non-pelleted (HG) or high-grain pelleted (HP) diets on the microbial structure and potential functions of digesta- and mucosa-associated microbiota in the jejunum of Hu sheep. Here, we randomly assigned 15 healthy male Hu sheep into three groups and fed the control diets (CON), HG, and HP diets, respectively. The experiment period was 60 days. The HP diets had the same nutritional ingredients as the HG diets but in pelleted form. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Through the screening of the correlation network diagram between species, the core species with the highest number of inter-species associations in CON was g_Mogibacterium , a pro-inflammatory bacterium present in the digestive tract of ruminants [ 73 ], and in the group supplemented with oregano essential oil, the core species was g_Ruminococcus , which plays a significant role in the rumen of ruminants in the production of short-chain fatty acids [ 74 ] and the degradation of cellulose [ 75 ]. This suggests that oregano essential oil modulates the structural function of rumen microbes in calves and promotes gastrointestinal digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Through the screening of the correlation network diagram between species, the core species with the highest number of inter-species associations in CON was g_Mogibacterium , a pro-inflammatory bacterium present in the digestive tract of ruminants [ 73 ], and in the group supplemented with oregano essential oil, the core species was g_Ruminococcus , which plays a significant role in the rumen of ruminants in the production of short-chain fatty acids [ 74 ] and the degradation of cellulose [ 75 ]. This suggests that oregano essential oil modulates the structural function of rumen microbes in calves and promotes gastrointestinal digestion.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that an increase in the abundance of Olsenella was considered to improve immunity in calves [ 21 ]. Moreover, Olsenella was also considered to strengthen the immunoregulation capacity of a goat model [ 22 ] and mouse model [ 23 ] host. Similarly, Limosilactobacillus has been proved to have antibacterial and intestinal immunity-enhancing effects [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 A). Chitinophagales are rarely detected in gut [ 56 , 57 ], and to our knowledge, have not been documented in plant polymer decomposition in paddy soils. Currently, only a small number of Chitinophaga species have been isolated and characterized from soil environments [ 58 60 ] and most of these cultured species are aerobes that respire plant sugar polymers with oxygen [ 61 63 ].…”
Section: Discussionmentioning
confidence: 99%